A two-level parallelization method for distributed hydrological models. (June 2016) - Liu, Junzhi; Zhu, A-Xing; Qin, Cheng-Zhi; Wu, Hui; Jiang, Jingchao
Abstract: This paper proposes a scalable two-level parallelization method for distributed hydrological models that can use parallelizability at both the sub-basin level and the basic simulation-unit level (e.g., grid cell) simultaneously. This approach first uses the message-passing programming model to dispatch parallel tasks at the sub-basin level to different nodes with multi-core CPUs in the cluster. Each node is responsible for some of the sub-basins. Parallel tasks for each sub-basin at the basic simulation-unit level are then dispatched to multiple cores within each node using the shared-memory programming model. A grid-based distributed hydrological model was parallelized to demonstrate the performance of the proposed method, which was tested in different scenarios (e.g., different data volume, different numbers of sub-basins). Results show that the proposed two-level parallelization method had better scalability than the parallel computation at sub-basin level alone, and the parallel performance increased with data volume and the number of sub-basins. Highlights: Two-level parallel-computing was conducted for a distributed hydrological model. The parallelizability at both sub-basin and basic simulation unit level was used. Hybrid parallel computing was conducted on multi-core clusters. A grid-based model was parallelized to illustrate the method. Two-level parallel computation has good scalability.